PENGARUH PRODUKTIVITAS KERJA TERHADAP KINERJA KARYAWAN PDAM TIRTA SEJUK (STUDI PADA BAGIAN HUBUNGAN PELANGGAN) - Arwin Arwin; Said Hamzali (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research was conducted to determine the effect of employee work productivity on employee performance in the customer relations department. The purpose of this study was to determine and analyze how employee productivity, how employee performance, and how much influence work productivity has on employee performance in the customer relations department. This research uses quantitative methods with descriptive research type. Sampling was done by non-probabilty sampling method, with the number of respondents as many as 53 people. The data analysis technique used is descriptive analysis and simple linear regression analysis. Based on the results of the hypothesis test (t test), it was found that the work productivity variable had a significant effect on the performance of the employees of the customer relations department .Based on the coefficient of determination, it was found that the work productivity of customer relations department employees was able to explain the employee's performance by 68.8% and the remaining 31.2% was influenced by other factors not examined in this study such as remuneration factors and others.